214 A TL1 Team Approach: Physician Strategies to Promote Physical Activity Among Youth with Comorbid Asthma and Overweight/Obesity - Natalie C. Koskela-Staples; Jacqlyn L. Yourell; MS Jennifer L. Doty; David A. Fedele (Journal of Clinical and Translational Science, 2022)
OBJECTIVES/GOALS: Youth with comorbid asthma and overweight/obesity (OW/OB) are at risk for increased morbidity. Physical activity (PA) engagement can mitigate risks, but the majority of youth do not meet national PA guidelines. This study examines caregiver and youth perspectives about ways physicians can promote PA in this population. METHODS/STUDY POPULATION: Participants included 20 adolescents (M age = 16.0; 55% male) with asthma and OW/OB and a primary caregiver (90% mothers). Caregivers and adolescents participated in separate semi-structured interviews about adolescent PA engagement, including questions regarding strategies for physicians to promote PA. Interviews were audio recorded, transcribed, and analyzed using NVivo. Two authors assigned conceptual codes to the transcripts to identify key concepts and then met to create a codebook. Authors independently coded 4 transcripts and met to resolve discrepancies. Authors then independently coded 2 additional transcripts (final kappa = .62) and met to reach consensus before dividing the remainder for coding. Codes were collapsed and sorted into themes, and attributes of each theme were determined. RESULTS/ANTICIPATED RESULTS: Dyads discussed the importance of physicians providing general (positive statements) and PA-specific encouragement. Dyads also stated that physicians should encourage teens to set and reach PA-related goals. Caregivers and youth reported that physicians should provide education about the importance of PA and ways to engage in PA, awareness about adolescents weight and its impact on health, and resources (camps, events, and locations). Additionally, caregivers and a teen noted that physicians should talk directly to and address questions toward teens. Dyads mentioned the importance of focusing on overall health (instead of weight) as well. Dyads also noted that physicians should avoid judgmental and shaming statements when talking about weight. DISCUSSION/SIGNIFICANCE: Results provide information about strategies physicians can use to promote PA among adolescents with asthma and OW/OB, a population that is at risk for low PA and poor health outcomes. Findings suggest that physicians may effectively motivate behavior change by providing health guidelines, encouragement, resources, and positive reinforcement.